PENGARUH TEKNIK THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Febrianti, Mega; Tressyalina, Tressyalina; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this research is (1) to find out the level of writing skills the text of the report on the results of observation Class VII students of SMP Negeri 34 Padang without using the technique think talk write . (2) to find out the level of writing skills text reports the results of an observation grade VII SMP Negeri 34 Padang the field by using the techniques think talk write. (3) analyse the influence of the techniques think talk write against writing skills text reports the results of an observation grade VII SMP Negeri 34 Padang. Type of this research is quantitative with the method of experimentation. Based on the data analysis, the use of the techniques think talk write against writing skills text reports the results of an observation grade VII SMP Nefgeri 34 Padang better use of on before using the techniques think talk write. Kata kunci: pengaruh, teknik think talk write, teks laporan hasil observasi